Hy-Game (Honesty Game) As An Anti-Corruption Learning Media For Children - Rahman, Malik Akbar Mulki; Asror, Muhammad Hisyam (Law Research Review Quarterly, 2019)
Corruption is an act that is not commendable because it can harm yourself and others, according to the Corruption Eradication Commission in Indonesia in 2018 experienced a decline of 29.8 percent from 38.2 percent. Despite the decline we still have to prevent corruption in order to make the Indonesian state better. To prevent corruption, we can apply anti-corruption cultural values ​​in our daily lives, including the values ​​of honesty, fairness, courage, simple living, responsibility, discipline, hard work, saving and being independent. We can apply these values ​​as a reference in carrying out daily activities so that the work we do is beneficial and blessing, in addition to applying these values, we can make a preventive effort on the culture of corruption to children as future generations by utilizing technology In today's modern era, we have been facilitated by technological sophistication to carry out activities so that we can use them for positive things by developing an anti-corruption game that is integrated with gadgets so that through this media can prevent a culture of corruption for generations to come.